Effect of different mixing and kneading process on the quality characteristics of frozen cooked noodle. (March 2019) - Shao, Li-Fang; Guo, Xiao-Na; Li, Man; Zhu, Ke-Xue
Abstract: In this study, the impact of different mixing and kneading processes on the qualities of frozen cooked noodle were evaluated, including freezable water content and microstructure of the noodle, as well as rheological properties of dough. The results showed that the frozen cooked noodle of manual dough mixing (MM) scored the highest in sensory evaluation, while the one via vacuum dough mixing (VM) way had the best texture and cooking properties with lower water absorption and cooking loss under the same kneading process. The vacuum condition could contribute to a more uniform and continuous matrix of protein during the mixing process. Besides, both machine kneading (MK) and hand kneading (HK) process displayed a significant ( p < 0.05) positive effect on the qualities of frozen cooked noodle, such as texture properties, cooking properties, and sensory score. Furthermore, the role of hand kneading process was more evident than machine kneading. Highlights: Systematic study of mixing and kneading process on the effects of noodle's quality. Frozen cooked noodle's qualities were significantly improved by vacuum mixing. Kneading process was benefit for the high qualities of frozen cooked noodle. Hand kneading process has the most significant effect on the noodle's qualities.